1994
DOI: 10.1002/art.1780370418
|View full text |Cite
|
Sign up to set email alerts
|

Association between antiphospholipid antibodies and epilepsy in patients with systemic lupus erythematosus

Abstract: Objective. To determine whether the occurrence of seizures is correlated with the presence of serum antiphospholipid antibodies (aPL) in systemic lupus erythematosus (SLE) patients.Methods. The study included 221 unselected patients with SLE. Of these, 21 patients with epileptic seizures not attributed to any cause other than SLE were identified. Epilepsy was diagnosed by clinical history and electroencephalography. Blood samples were tested for the presence of antibodies to cardiolipin (aCL, IgG and IgM isoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
2
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(73 citation statements)
references
References 15 publications
(14 reference statements)
6
60
2
5
Order By: Relevance
“…A significant association has been reported between aPL and recurrent ischemic events, strokes, or transient ischemic attacks (7)(8)(9)(10). Likewise, several studies have reported the existence of a link between aPL and seizures in patients with SLE or in patients with the primary syndrome (11,12). Ocular disturbances (amaurosis fugax [2,13] and optic atrophy [2]), multiinfarct dementia, dementia of nonischemic origin (6,14,15), and chorea (16) have also been reported in patients with primary APS.…”
Section: Introductionmentioning
confidence: 97%
“…A significant association has been reported between aPL and recurrent ischemic events, strokes, or transient ischemic attacks (7)(8)(9)(10). Likewise, several studies have reported the existence of a link between aPL and seizures in patients with SLE or in patients with the primary syndrome (11,12). Ocular disturbances (amaurosis fugax [2,13] and optic atrophy [2]), multiinfarct dementia, dementia of nonischemic origin (6,14,15), and chorea (16) have also been reported in patients with primary APS.…”
Section: Introductionmentioning
confidence: 97%
“…In that description, several neuropsychiatric features (headache, migraine, epilepsy, chorea, and cerebrovascular events such as stroke, transient ischemic attacks, visual field defects, and progressive cerebral ischemia) were noted (3). To date, APS has been associated with cerebrovascular disease (4), dementia (5), epilepsy (6,7), headaches/migraines (8), transverse myelitis, cognitive dysfunction (9), chorea (10), psychosis (11), optic neuropathy (12), and sensorineural hearing loss (13). The international (Sapporo) classification criteria (14) for APS include cerebrovascular disease, when it is documented on brain magnetic resonance imaging (MRI) as stroke or small-vessel disease.…”
mentioning
confidence: 99%
“…Bu konuda yapılan araştırmalar en azından, SLE hastalarında izlenen nörolojik tutulumdan sorumlu en önemli faktörün anti-fosfolipid antikorlarının olmadığını telkin etmektedir. [13][14][15] NP-SLE'de beyinde aseptik menenjit ve vaskülite sekonder iskemik ve demiyelinizan lezyonlar izlenebilir. Lezyonlu hastalarda parenkimal irritasyon zemininde semptomatik epilepsi de ortaya çıkabilmektedir.…”
Section: Sistemik Lupus Eritematozusunclassified